THE EARLY JURASSIC FAUNA FROM THE GURUMDY AND MYNHAJIR ZONES OF THE EAST PAMIRS - Melnikova G.K. (My University, 2006)
The Southeast Pamirs is a unique region with a wide development of Jurassic marine sediments that are characterized by complete different-facies sections and diverse fossils. Of particular interest are Early Jurassic corals, which represent the first finds in mountainous Central Asia and the entire eastern Mediterranean belt. Finds of such fossils are extremely rare in other regions of the world so far.
Keywords: Мезозой::Юрская; Mesozoic::Jurassic